Akt mowy groźba – klasyfikacja i definicja: ujęcie pragmalingwistyczne (na materiale języka polskiego i rosyjskiego) - Komorowska, Ewa; Stanulewicz, Danuta (Przegląd Wschodnioeuropejski, 2025)
So far, the speech act of threat has attracted relatively little attention from researchers. Moreover, there is no agreement as to its definition and classification. The aim of this paper is to place threatening in the classification of speech acts and to attempt at defining it. We emphasize the complexity of threatening which may be classified as a directive speech act, although – being a “negative” promise – it exhibits some characteristics of commissives. In the case of a promise, it is the addressee who is the beneficiary, whereas in the case of a threat, the demanded behaviour is in the interest of the sender. Moreover, the speech act of threat is associated with evoking fear in the addressee.